TINGKAT DISIPLIN BERLALU LINTAS REMAJA MILENIAL DI KECAMATAN NGORO KABUPATEN JOMBANG - Hesty Eka Pratiwi; Maya Mustika Kartika Sari (Universitas Negeri Surabaya (Unesa), 2023)
This study aims to describe the level of traffic discipline of millennial adolescents in Ngoro District, Jombang Regency. The research approach used is quantitative with a descriptive design. Data was collected through questionnaires using a likert scale type that used four answer choice options. Sampling technique using non probability sampling: incidental. The distribution of the questionnaire was carried out by providing questionnaires online or through the researcher's social media in the form of Facebook. The population used was 10,705 with a sample of 100 respondents. The sample criteria taken by the researchers were millennial teenagers who are residents of Ngoro District, driving two-wheeled motorized vehicles, usually using the internet and ranging in age from 15-24 years. The data analysis technique in this study uses percentage techniques and is based on Thomas Lickona's theory which states that when a person knows a good thing, wants a good thing, and does a good thing, a good character will be formed as well. There are three indicators used as benchmarks in the study. The overall results showed that the level of traffic discipline of millennial teenagers in Ngoro District was classified as good, with details of 80 respondents (80%) having a good level of traffic discipline and the remaining 20 respondents (20%) having a fairly good level of traffic discipline and none of the respondents having a relatively poor level of traffic discipline. The total score obtained was 10,268 with an average of 102.68 which is good. This means that millennial teenagers in Ngoro District have a high level of discipline in traffic. Keywords:Youth, Millenials, Traffic Discipline